Realization of Accurate Load Impedance Characterization for On-Wafer TRM Calibration - Su, Jiangtao; Wang, Jianhua; Wang, Fei; Sun, Lingling (Frontiers in Physics, 2021)
In this paper, the uncertainty and the impact of imperfect calibration standard for on-wafer Through-Reflect-Match (TRM) calibration algorithm is analyzed with the help of 3-D electromagnetic simulations. Based on the findings that load impedance can lead to significant errors in calibration, an automatic algorithm to determine the complex impedance of the load standard is proposed. This method evaluate the resistance as well as the parasitic inductance introduced by the misalignment of probe tip to substrate pad at mm-wave frequencies or the non-precise load. The proposed method is verified by practical measurement and the results show that by incorporating actual load impedance into the calibration algorithm, the deviations of RF measurement results is greatly suppressed.